Economic diplomacy of Russia towards Venezuela: From H. Chaves to N. Maduro - K. A. Isaev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Bolivarian Republic of Venezuela faces a deep political and economic crisis that is exacerbated by severe restrictive measures imposed against it by the United States and their allies. In these circumstances, the availability of external economic support becomes particularly important. In recent years, Russia has become one of the key donors for Venezuela with a wide range of economic diplomacy tools at its disposal. Drawing upon official data, as well as recent findings of Russian and foreign researchers, the present paper examines the evolution of Russian economic diplomacy towards Venezuela during the presidency of H. Chavez (1999–2013) and N. Maduro (2013 — present). The author emphasizes that bilateral economic cooperation was already institutionalized under H. Chavez. The most intense interaction took place in the energy and military-technical fields. The mechanisms of Russian economic diplomacy included primarily public and private loans, investments, and payments for the permission to develop Venezuelan oil deposits. The election N. Maduro was accompanied by a dramatic deterioration of political and economic situation in the country. The crisis was further aggravated by economic sanctions imposed by the US. The latter also affected Russian projects in the republic. However, Russia continued to provide significant support to Venezuela, both through already proven mechanisms of economic diplomacy and a number of new ones, including sovereign debt restructuring and advance delivery of goods. At the same time, the author notes that this assistance remains rather isolated and limited, it affects only specific areas, mainly oil and gas and military-technical cooperation, and its volume is insufficient to effectively address the economic crisis in Venezuela. In this context, the domestic economic policy of the Venezuelan government is of particular importance. Indeed, liberal economic reforms carried out since 2018 were helpful for recovery from the economic crisis. In this connection, the author provides a list of measures and mechanisms Russia could implement in the framework of economic diplomacy to ensure this positive trend.